Characterization and in situ bioprotective efficacy of reuterin E81 produced by Limosilactobacillus reuteri E81 in white cheese model - Ispirli, Humeyra; Ozturk, Hale Inci; Dertli, Enes (ELSEVIER, 2025)
This study focused on characterization and in situ application of reuterin E81, a potent antimicrobial compound produced by Limosilactobacillus (L.) reuteri E81, in white cheese. Strain E81 harbored the gene island containing pdu-cbi-cob-hem clusters responsible for reuterin production and this led to investigation of reuterin production for this strain. Initially, reuterin was synthesized from glycerol and characterized using NMR and FT-MIR analyses. Specific 1H and 13C NMR peaks confirmed the presence of reuterin components such as 3-hydroxypropionaldehyde and acrolein, while FT-MIR spectra indicated a distinct carbonyl (C=O) stretching band at 1717 cm-1, characteristic of aldehyde groups of reuterin system. Reuterin E81 showed dose dependent fungistatic and bactericidal effects, with complete inhibition of Gram-negative ones at lower doses. In white cheese production, four groups were prepared, including control and experimental groups with or without glycerol addition. The challenge test conducted over 30 days of cold storage demonstrated that white cheese samples containing L. reuteri E81 and glycerol achieved a significant reduction in microbial loads, with Escherichia (E.) coli counts decreasing from 6.4 log CFU/g to undetectable levels, which was attributed to in situ reuterin production. Meanwhile, total aerobic mesophilic bacterial counts declined progressively. These findings highlight the potential of in situ reuterin production as a natural strategy to enhance the microbiological safety of white cheese. However, it also inhibited the growth of S. thermophilus and L. reuteri cultures. The inhibitory effects of reuterin on beneficial lactic acid bacteria suggest the need for further optimization to balance food safety with starter culture viability.
Keywords: Protective culture; Clean label; Antimicrobial activity; Challenge test; E. coli; ESCHERICHIA-COLI O157H7; LACTOBACILLUS-REUTERI; FERMENTED MILK; GLYCEROL; MICROORGANISMS; PATHOGENS; NISIN; Food Science & Technology